2020
DOI: 10.3389/fpsyg.2020.01875
|View full text |Cite
|
Sign up to set email alerts
|

A Path Toward Inclusive Social Cohesion: The Role of European and National Identity on Contesting vs. Accepting European Migration Policies in Portugal

Abstract: The Western hemisphere has witnessed recent increased immigration flows generating social and political debate across Europe. In one view, migration flows represent an opportunity to construct a diverse social cohesion. In another view, migration flows are perceived as a threat to existent national cultures. This view is held by political nationalisms and right-wing populist forces installed in the majority of EU countries' parliaments, accentuating discrimination against immigrants and residents in Europe. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Thomas et al, 2022). Additionally, it confirms the results of numerous studies showing that identification with a group is a moderately strong predictor of households’ pro-environmental behaviours (Fielding & Hornsey, 2016; Keshavarzi et al, 2021), citizens’ willingness to integrate with immigrants (Pinto et al, 2020), approval for racial equity (Selvanathan et al, 2018) and supportive attitudes towards different sexual orientations (Górska et al, 2017). Moreover, we shed light on the validity of incorporating the concept of opinion-based group identity to explore the motivations of social activists in cyberspace.…”
Section: Discussionsupporting
confidence: 86%
“…Thomas et al, 2022). Additionally, it confirms the results of numerous studies showing that identification with a group is a moderately strong predictor of households’ pro-environmental behaviours (Fielding & Hornsey, 2016; Keshavarzi et al, 2021), citizens’ willingness to integrate with immigrants (Pinto et al, 2020), approval for racial equity (Selvanathan et al, 2018) and supportive attitudes towards different sexual orientations (Górska et al, 2017). Moreover, we shed light on the validity of incorporating the concept of opinion-based group identity to explore the motivations of social activists in cyberspace.…”
Section: Discussionsupporting
confidence: 86%
“…In exploring the factors influencing immigrant integration, scholars have not only focused on socio-economic conditions [89], but also explored the effects of digital communication technologies [87], religion [97,98], education [95], and host country attitudes toward immigrants [99][100][101]. Studies of China's agricultural migrants have divided their integration into urban society into three stages, including circular migration, urban settlement, and urban integration, in which the economic status of urban and rural migrants, the expansion of social welfare, and the social interaction between agricultural migrants and urban residents are key factors influencing the transition between these stages [92].…”
Section: Empirical Studies Of Social Integrationmentioning
confidence: 99%
“…Cuadros et al ( 2020) study in this issue shows structural validity of collective esteem scale, in a sample of students, and it he vein positive effects of collective identity; found that collective esteem correlates with personal and social wellbeing. Pinto et al (2020) bring an important nuance to the issue of social identity and social wellbeing -national and supranational in its case. They find that the European supranational identity is associated with a lesser rejection of immigrants and a wellbeing, in the sense of a climate of prosocial behavior and migrant's inclusion.…”
Section: Social Belongingness and Social Identificationmentioning
confidence: 99%